2007
DOI: 10.1179/oeh.2007.13.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Characteristics of Small Metal-Fabricating Businessesin Minnesota

Abstract: Small U.S. businesses are underserved in terms of occupational health and safety (OHS) services. Little is known about organizational factors influencing OHS in these establishments. Machine guarding was quantitatively evaluated in 40 small businesses. Checklists were used to develop safety scores. Organizational information such as number of employees, unionization, and number of machines was obtained. Experience modification rates, annual sales, and credit ratings were also obtained. Safety scores were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Norwegian employers, including small businesses in construction and manufacturing are mandated to offer occupational health services to their workers [NLIA, 2010]. Samant et al [2007] documented the preventive effect of safety committees in reducing the risk of exposure to machine related hazards in small manufacturing businesses. The International Labor Organization (ILO) has underscored the critical role of the occupational health services in preventing work-related injuries [Fedotov, 2005].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Norwegian employers, including small businesses in construction and manufacturing are mandated to offer occupational health services to their workers [NLIA, 2010]. Samant et al [2007] documented the preventive effect of safety committees in reducing the risk of exposure to machine related hazards in small manufacturing businesses. The International Labor Organization (ILO) has underscored the critical role of the occupational health services in preventing work-related injuries [Fedotov, 2005].…”
Section: Recommendationsmentioning
confidence: 99%
“…The integration of a robust injury prevention program in occupational health services could yield significant preventive benefits. Samant et al [2007] documented the preventive effect of safety committees in reducing the risk of exposure to machine related hazards in small manufacturing businesses. The Norwegian Work Environment Act mandates safety committees for businesses with more than 50 workers, while safety representatives elected by and from workers are mandated for businesses with more than 10 workers [NLIA, 2006].…”
Section: Recommendationsmentioning
confidence: 99%
“…In the MN‐MGS, regardless of size, businesses with safety committees were found to have better safety practices when compared to those without ( P < 0.004 for trend) [Samant et al, ]. The MN‐MGS found that 57% of participating businesses (n = 40) had a safety committee at baseline [Brosseau et al, ] compared with 37% in the NMGP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study was constrained by a small sample size. [Munshi et al, ; Samant et al, ; Parker et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…While workers at these plants are organised into at least one, and arguably more, level of organisation, department information was not available to us. We collapsed 56 plants into types according to the nature of the work done in the plant and modelled unionisation of the plants, with the hypothesis that stronger safety programming at unionised plants would result in lower injury rates 12 24. While we do not know if these plant-level variables are the most meaningful plant-level exposures in this workforce, by using available data from an existing survey, we have made some progress in parsing plants’ contributions to individuals’ injury rates.…”
Section: Discussionmentioning
confidence: 99%